The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.11648/j.avs.20150303.14
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Reproductive Performance and Problems in Crossbred (Holstein Friesian X Zebu) Dairy Cattle in and Around Mekelle, Tigray, Ethiopia

Abstract: with the aims to assess reproductive performance and prevalence of reproductive problems in crossbred (Holstein Friesian x Zebu) dairy cattle. A questionnaire survey methodology was used. The study sampled 177 randomly selected dairy farms comprising 1013 crossbred dairy cattle (736 cows and 277 heifers). The mean age at first service, age at first calving, first postpartum estrus and calving interval were 24.8 months, 35.3 months, 114.5 days and 401.5 days, respectively. Prevalence rates of reproductive probl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 18 publications
3
8
3
Order By: Relevance
“…Although results from the current study indicated that the majority of farmers visually observed for heat in cows, this method alone is not efficient. This case was also observed by Harlow et al (2015) who reported that there were high incidences for farmers missing the opportunity to either inseminate or mate their animals when they use visual inspection. This is because farmers in mixed crop-livestock systems, which is common to small-scale farmers, tend to spend less time in the cow sheds and are therefore less likely to see cows in estrus.…”
Section: Discussionsupporting
confidence: 76%
“…Although results from the current study indicated that the majority of farmers visually observed for heat in cows, this method alone is not efficient. This case was also observed by Harlow et al (2015) who reported that there were high incidences for farmers missing the opportunity to either inseminate or mate their animals when they use visual inspection. This is because farmers in mixed crop-livestock systems, which is common to small-scale farmers, tend to spend less time in the cow sheds and are therefore less likely to see cows in estrus.…”
Section: Discussionsupporting
confidence: 76%
“…Grunert, (1986) observed that retained placenta due to apart from bacterial infection, may also be caused by hormonal and nutritional imbalance, housing system and stress at the time of calving, difficult delivery, premature and induced birth and twinning. Mekonnin et. al.…”
Section: Resultsmentioning
confidence: 99%
“…The recommended body weight of Holestin at the first service is 340 kg. Holestin cattle reach puberty at about 37.21 months of age [10] than their cross with zebu which reach puberty at about 24.8 months of age [16].…”
Section: Age At First Service (Afs)mentioning
confidence: 99%